COMPARATIVE ANALYSIS OF PHRASEOLOGICAL UNITS RELATED TO THE RELIGIOUS SPHERE IN GERMAN AND UZBEK LANGUAGES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes phraseological units in German and Uzbek from an anthropocentric perspective, and studies phraseologisms related to the religious sphere in both languages from a comparative perspective.